Collected works (gsuṅ-ʼbum) of Sgo-maṅ Mkhan-chen Mkhyen-rab-bstan-pa-chos-ʼphel - Mkhyen-rab-bstan-pa-chos-ʼphel, Sgo-maṅ Mkhan-chen, 1840-1908 (D. Gyaltsan & K. Legshay, 1972)
Writings on Tibetan Lamaism by a savant of the Gelukpa sect.